2010
DOI: 10.5459/bnzsee.43.3.202-212
|View full text |Cite
|
Sign up to set email alerts
|

The sliding hinge joint moment connection

Abstract: A new friction moment joint for steel framed structures is described. It has a similar cost to conventional construction and is designed such that there is negligible damage to the frame or slabs. Experimental testing shows that steel, brass or aluminium shims can provide satisfactory friction resistance and that there is almost no damage to the frame during design level displacements. A method for establishing the dependable friction force is developed considering construction tolerances and bolt moment-axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 11 publications
0
58
0
Order By: Relevance
“…Clifton and MacRae et al . tested brass and mild steel shims, respectively, showing similar behaviour. Mild steel shims are cheaper, can be tack welded to facilitate erection and avoid dissimilar metal corrosion issues.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Clifton and MacRae et al . tested brass and mild steel shims, respectively, showing similar behaviour. Mild steel shims are cheaper, can be tack welded to facilitate erection and avoid dissimilar metal corrosion issues.…”
Section: Introductionmentioning
confidence: 61%
“…μ n = V ss /2N proof ), with the V ss determined from experimental testing. Previous research reported a μ n = 0.21–0.22 for mild steel and brass shims with M24 and M30 bolts. Further testing is required to determine μ n for abrasion resistant steel shims using a range of specimen sizes.…”
Section: Asymmetric Friction Connectionmentioning
confidence: 94%
See 3 more Smart Citations